Friction and deformation at convergent contacts in geotribological systems - Emilia Assenova; Evgenia Kozhoukharova (Tribology and Materials, 2022)
Geotribology reveals the application of a tribological approach to natural, e.g. nonmechanical inorganic tribosystems in the Earth's crust. It aims an integrated view over frictional phenomena in the Earth's crust and tracks the interweaving between the immense seismotectonic energy brought in and generated in the geotribological zones, and the evolution of destructive and constructive contact processes ending with the emergence of new mineral structures preserving system's life. A tribological application concerns the convergent contact deformations in geological objects with different rheology, in the movement of tectonic plates, leading to the emergence of obduction relief structures. Convergent geotribological contacts are places of tectonic collision between large rock plates forming the planetary zones of most active, both seismic and volcanic activity. A typical example is the obduction and subduction zones of two ongoing rock plates, one pushing under the other. Studies of the contact process in geotribozones provide an opportunity for tribology to explain new phenomena in the variety of contact deformations and their full cycle of evolution. Considering the necessity of using a tribological approach to geology when describing friction-induced deformations, the role of rheology, mechanisms of preliminary contact displacement and distribution of energy and energy density in the contact body is shown.